Mineral phosphate solubilization of rhizobia and endophytic nodule bacteria of legumes. - Mohd Saud, Halimi; M. K., Nur Hasnidar (2012)
Nitrogen and phosphorous are two of the main elements required for plant growth. Beneficial microorganisms can supply nitrogen through biological nitrogen fixation and increase P uptake by P solubilization of mineral phosphates through the production of organic acids. Rhizobium is a well established biological nitrogen fixer but other potential characteristics that promote overall plant growth have been largely ignored. A study was carried on rhizobia and root nodule endophytes from legumes to determine their phosphate solubilizing ability using solid and broth media containing mineral phosphates. A total of 160 rhizobia and root nodule endophytes were tested. Only 42 isolates (26.25%) showed phosphate solubilization activity using solid agar media and from these, a further 14 isolates were studied based on growth in various liquid mineral phosphate media. Isolate GM 119, a root nodule endophyte from Glycine max, showed the best result for phosphate solubilization on media containing Ca,(P04)2.